Outsourcing of unionized firms and the impact of labor market policy reforms - Erkki Koskela; Ronnie Schöb (Institute for the Study of Labor (IZA), 2008)
This paper shows that outsourcing of parts of workforce in unionized firms leads to wage moderation both in the case of strategic and flexible outsourcing and as long as the share of the outsourced workforce is not too large, this wage-moderation effect on domestic employment outweighs the direct substitution effect so that domestic employment increases in unionized firms as outsourcing costs fall. With respect the impact of labor tax reforms that are well-established in the literature: changes in the wage tax rate, the tax exemption and the unemployment benefit payments affect domestic wage setting in the same way as in the absence of outsourcing. Furthermore, increasing the degree of tax progression by keeping the relative tax burden per worker constant continues to be good for employment. However, except for low outsourcing activities, the impact of these policy measures will become smaller as outsourcing costs fall.
urn:nbn:de:101:1-2008070212
Keywords: J41; 330; Outsourcing; union wage-setting; employment; labor tax reform; Arbeitsmarkt; Outsourcing; Lohnniveau; Beschäftigungseffekt; Gewerkschaftlicher Organisationsgrad; Lohnsteuer; Steuerreform; Theorie